Seed germination behaviour of Terminalia paniculata Roth (Combretaceae), an economically important endemic tree to peninsular India - Viswanath, Sanal C; Pillai, P K C; Francis, Sinny; Hrideek, T K (Current Botany, 2021)
The present study was conducted to investigate the seed germination behaviour of Terminalia paniculata, a commercially important tree component of deciduous forests of Peninsular India. The study included the identification of maturity index to determine the optimum collection period of the most viable seeds with good seed longevity. Species are characterized by very low germinability and poor regeneration status. Observations were made throughout the flowering and fruiting period on selected matured trees. Seed viability was tested at various stages of maturity and seed longevity was evaluated. The results indicated that the 16th week after anthesis with red-colored fruits recorded the maximum viability (2.60% germination) that shows it is the best period for the collection of seeds. Seed emptiness is very high in T. paniculata (4 to 2%) compared to other Terminalia species (low emptiness). Pre-sowing treatments were not effective in enhancing seed germination and viability. Seeds can be stored up to 6 months in an air-tight metallic container at 4oC and 45 ± 5 % relative humidity. The results of the study can be taken as a reference for various other tree improvement programs and further studies.